Electronic Marketing and Service Quality of On-Line Merchandisers: A Case Study of Jumia Uganda. - Ssemaluulu, Paul Mukasa; Isingoma, Fenehansi; Mugavu, George (Kabale University, 2024)
The study examined electronic marketing and service quality of on-line merchandisers: a case study of Jumia Uganda. The specific objective was to find out the relationship between cart abandonment rate and service quality in Jumia Uganda. The research employed a cross- sectional survey design to investigate the association between electronic marketing efforts and service quality. A mixed-methods research approach, incorporating both quantitative and qualitative methodologies, was deemed highly relevant for this study. In addition, from the 255 target respondents, a definite sample size of 101 was determined using William G. Cochran (1997) formula. The study revealed significant correlations between various factors in the context of Jumia Uganda's electronic marketing. The study revealed that a moderate positive correlation (r = 0.422**) was identified between cart abandonment rate and service quality, emphasizing the critical role of service quality in customer retention and reducing cart abandonment. It was recommended that: Jumia should launch remarketing campaigns to re-engage customers who abandoned their carts. Personalized messages and incentives should be used to encourage them to return and finalize their transactions.